1987
DOI: 10.1128/jb.169.2.670-674.1987
|View full text |Cite
|
Sign up to set email alerts
|

Operator-constitutive mutations of the Escherichia coli metF gene

Abstract: The Escherichia coli metF gene codes for 5,10-methylene-tetrahydrofolate reductase, the enzyme that leads to the formation of N-methyltetrahydrofolate, supplying the methyl group of methionine. Transcription of metF, as well as of most of the methionine genes, is repressed by the metj gene product complexed with S-adenosylmethionine. A metF'-'lacZ gene fusion was used to isolate mutants that have altered expression from the metF promoter. The nuicleotide sequences of the metF regulatory region from five such m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The first four amino acids of the MetE protein from E. coli and S. typhimurium are identical (18,29), and the present results show that 16 of the first 18 amino acids of the MetR protein in both organisms are also identical (18). Seven potential regulatory met boxes (3)(4)(5)(6)(7) (that contain at least 50% identity with the met box consensus sequence, 5'-AGACGTCT-3') are overlined in the sequence shown in Fig. 2.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…The first four amino acids of the MetE protein from E. coli and S. typhimurium are identical (18,29), and the present results show that 16 of the first 18 amino acids of the MetR protein in both organisms are also identical (18). Seven potential regulatory met boxes (3)(4)(5)(6)(7) (that contain at least 50% identity with the met box consensus sequence, 5'-AGACGTCT-3') are overlined in the sequence shown in Fig. 2.…”
mentioning
confidence: 56%
“…Considerable knowledge has been obtained at the molecular level on the mechanism of this regulation. Studies on the expression of several of the met genes have shown that a repressor protein, the product of the metJ gene, can bind to a specific region on the DNA (met box) that is present in all met genes thus far examined (3)(4)(5)(6)(7). This interaction of the MetJ protein with the met operator region is markedly enhanced by the presence of S-adenosylmethionine (AdoMet), a primary metabolic product of methionine (5,8,9).…”
mentioning
confidence: 99%
“…7a), (ii) is highly de-repressed in our RNA-seq analysis in DyeaG bacteria ( Fig. 4c and Table S4), and (iii) is widely used for in vitro analyses of MetJ-DNA interactions [24,25]. As shown in Fig.…”
Section: Aberrant Activation Of the Methionine Biosynthesis Pathway Amentioning
confidence: 83%
“…The pertinent DNA sequences of the metA, metC, metF, and metJ/metBL promoter regions contain from two to five imperfect, tandem repeats of the Met-box consensus sequence (3,4,7,18,24,25). The homology of individual Met-box sequences varies significantly within and between met regulon elements (3, 4).…”
mentioning
confidence: 99%